Improvisation of SDLC Model Using Machine Learning Technique (CBR) For Development of Software - Kumar, Madhup; Sharma, Anuradha (International Journal of Computer Sciences and Engineering, 2019)
This paper explores software development through early prediction of planning phase . It summarizes a variety of techniques for software planning prediction in the domain of software engineering. The objective of this research is to apply the various machine learning approaches, such as Case-Based Reasoning and Fuzzy logic, to predict software planning. The system predicts the planning phase activity after accepting the values of certain parameters of the software. This paper advocates the use of case-based reasoning (i.e., CBR) to build a software development prediction system with the help of human experts. The prediction is based on analogy. We have used different similarity measures to find the best method that increases reliability. It can be readily deployed on any configuration without affecting its performance.